2017
DOI: 10.1074/jbc.m116.768010
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation Controls Prion Fate in Vivo

Abstract: Edited by Paul E. Fraser Prions or PrPSc are proteinaceous infectious agents that consist of misfolded, self-replicating states of a sialoglycoprotein called the prion protein or PrP C . The current work tests a new hypothesis that sialylation determines the fate of prions in an organism. To begin, we produced control PrP Sc from PrP C using protein misfolding cyclic amplification with beads (PMCAb), and also generated PrP Sc with reduced sialylation levels using the same method but with partially desialylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…Our previous studies proposed that sialylation of PrP Sc N-linked glycans plays an important role in controlling the fate of prions in an organism [18,21]. In support of this hypothesis, we showed that animals inoculated with PrP Sc with reduced sialylation levels via intracranial or intraperitoneal routes lack any clinical or subclinical signs of prion disease, live healthy lives, and have undetectable levels of PrP Sc [19][20][21]. Considering that the sialylation status of PrP Sc is essential for determining its fate, it is important to investigate the cellular mechanisms that one can target for manipulating sialylation status of PrP C and PrP Sc .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our previous studies proposed that sialylation of PrP Sc N-linked glycans plays an important role in controlling the fate of prions in an organism [18,21]. In support of this hypothesis, we showed that animals inoculated with PrP Sc with reduced sialylation levels via intracranial or intraperitoneal routes lack any clinical or subclinical signs of prion disease, live healthy lives, and have undetectable levels of PrP Sc [19][20][21]. Considering that the sialylation status of PrP Sc is essential for determining its fate, it is important to investigate the cellular mechanisms that one can target for manipulating sialylation status of PrP C and PrP Sc .…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, SLOs represent silent reservoirs of prion infection, where PrP Sc could hide undetected for a life-time while possibly imposing a high risk of transmission through blood donation [41, 42]. Our recent studies revealed that the sialylation status of PrP Sc was critical for its effective trafficking to SLOs [20]. Within several hours following peripheral exposure of mice to prions, PrP Sc with unaltered sialylation status was found to be sequestered by spleen and lymph nodes, whereas partially desialylated PrP Sc was found predominantly in liver [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations